Dedication Thoroughbred Breeding Project (1940)
December 8, 1940. Left to Right: Henry P. Russell, president of the California Breeders' Association, Double-H Ranch, Carmel; B.K. Beckwith, field secretary, California Breeders' Association, East Pasadena; John J. Knezevich, public relations director, Hollywood Turf Club, Inglewood; Julian A. McPhee, president of California Polytechnic college; Charles E. Perkins, chairman committee, Alisal Ranch, Solvang; Carleton F. Burke, Greenfield Farm, Camarillo.